2015
DOI: 10.1111/jace.13709
|View full text |Cite
|
Sign up to set email alerts
|

Soft X‐ray Spectromicroscopic Investigation of Synthetic C‐S‐H and C3S Hydration Products

Abstract: Calcium silicate hydrates (C-S-H), the primary binding phase in concrete, is the most prominent physiochemical factor controlling the mechanical and chemical properties in the production of concrete. This paper reports the local-binding structure and morphological details of C-S-H as determined by high-resolution X-ray spectromicroscopy. Hydrated tricalcium silicate (C 3 S) was used to determine the properties and role of the outer products (Op) of C 3 S. C-S-H with different molar ratios of Ca/Si, were synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 54 publications
9
53
0
Order By: Relevance
“…The reference spectrum of the anhydrous C 3 S powder and Ca(OH) 2 is from our previous work [25]. In the present study, two different modes—line scan and image stack—were used for the in situ and ex situ NEXAFS measurements, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference spectrum of the anhydrous C 3 S powder and Ca(OH) 2 is from our previous work [25]. In the present study, two different modes—line scan and image stack—were used for the in situ and ex situ NEXAFS measurements, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The scanning transmission X-ray microscopy (STXM) technique has been successfully employed in numerous applications [20,21,22], including cement chemistry [23,24,25]. Recently, in situ soft X-ray spectromicroscopy using wet cells created by sandwiching a sample between two silicon nitride (Si 3 N 4 ) windows has been widely utilized for investigating wet samples [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Ca L 3,2 -edge, scale bar length 500 nm: absorption image of (a) C 3 S1.5 and (b) C 3 S50; (c) NEXAFS spectra of hydrated C 3 S samples, compared with that of pure CH. Spectrum of CH is from [44]. Table 3 Peak characters from the Ca L-edge spectra, some data are from [36,37].…”
Section: Ca L 32 -Edgementioning
confidence: 99%
“…At the nano-scale, Jennings [11] suggested that the basic construction unit of C-S-H is a non-spherical globule whose dimension is around 5 nm. Constantinides and Ulm [12] applied this model successfully to Cement and Concrete Research 77 (2015) [36][37][38][39][40][41][42][43][44][45][46] their nano-indentation experiments. The TEM studies of hydrated C 3 S and pozzolanic material by Richardson [10] and Taylor [13] demonstrated that the outer product of hydrated C 3 S grain, at high Ca/Si ratio, is composed of long-thin particles but two-demensional foils in case of low Ca/Si ratio; the inner product is rather featureless.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, methods to measure their atomic-or molecular-scale behavior are required in a wide range of research fields. To date, spectroscopic methods such as X-ray [6], neutron [7] and optical beam [8] technologies have been widely used for investigating distributions of water and ions at solid-liquid interfaces. While these methods have a subnanometer-scale vertical resolution, their lateral resolution is a few orders of magnitude larger than the atomic scale.…”
Section: Introductionmentioning
confidence: 99%